2007
DOI: 10.1258/004947507782332838
|View full text |Cite
|
Sign up to set email alerts
|

Green pit viper (Trimeresurus albolabris and T. macrops) venom antigenaemia and kinetics in humans

Abstract: Green pit viper bite is a common public health problem in Southeast Asia. Although most patients experience only local swelling, some may suffer from severe systemic bleeding that can be delayed. Venom antigenaemia was measured by enzyme-linked immunosorbent assay and correlated with clinical findings in 42 patients. Initial venom antigenaemia was not predictive enough for clinical uses. A kinetic study (n = 27) showed highest levels at presentation and, then, progressive decline. The average half-life was 27.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 12 publications
(19 reference statements)
3
21
0
Order By: Relevance
“…These laboratory findings are consistent with the haemorrhagic clinical manifestations of envenomation by Trimeresurus species (Chan et al, 1993;Chotenimitkhun and Rojnuckarin, 2008;Cockram et al, 1990;Greene et al, 2017;Hutton et al, 1990;Rojnuckarin et al, 2007;Rojnuckarin et al, 1999;Tan et al, 2017a;Visudhiphan et al, 1989;Witharana et al, 2019;Wongtongkam et al, 2005). In particular, the venoms have been shown clinically to produce rapid and pronounced decrease in fibrinogen levels leading to a net anticoagulant state (Collet et al, 2000;Longstaff and Kolev, 2015;Ryan et al, 1999), which is consistent with the results presented here.…”
Section: Discussionsupporting
confidence: 91%
“…These laboratory findings are consistent with the haemorrhagic clinical manifestations of envenomation by Trimeresurus species (Chan et al, 1993;Chotenimitkhun and Rojnuckarin, 2008;Cockram et al, 1990;Greene et al, 2017;Hutton et al, 1990;Rojnuckarin et al, 2007;Rojnuckarin et al, 1999;Tan et al, 2017a;Visudhiphan et al, 1989;Witharana et al, 2019;Wongtongkam et al, 2005). In particular, the venoms have been shown clinically to produce rapid and pronounced decrease in fibrinogen levels leading to a net anticoagulant state (Collet et al, 2000;Longstaff and Kolev, 2015;Ryan et al, 1999), which is consistent with the results presented here.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, symptoms can recur in patients bitten by vipers because of slow absorption of the venom from the wound, as seen in this patient. 3,17 In addition, this patient had severely prolonged coagulation tests while his platelet count was relatively normal. These results were compatible with the kinetic study of venom antigen of green pit viper that showed early prolongation of coagulation test but delayed thrombocytopenia.…”
Section: Discussionmentioning
confidence: 88%
“…3,7,14,17 The color of the latter 2 species is darker than the former. 3,7 The toxin of green pit viper acts like thrombin that can cleave fibrinogen but has no effect on fibrinopeptide B of fibrinogen.…”
Section: Discussionmentioning
confidence: 97%
“…The main feature of its venom is its high proteolytic activity which is thought to be responsible for most of the local and systemic effects observed following envenoming by this snake [20,38,39]. Some components have been isolated, identified and cloned from the venom of this species in Thailand to understand their effects [20,21,40], but the venom of this same species in China has not been extensively studied and identified, although one component (Chitribrisin, a TLE) was previously cloned in our laboratory [9]. In the current study, through three chromatographic steps, a new TLE, TA-2, was isolated and purified from the venom of the Chinese T. albolabris and it could be inferred that the yield of TA-2 was about 1.2% (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, several TLEs have been identified and isolated from the venoms of T. gracilis, T. stejnegeri and T. albolabris, and some TLEs have been cloned [9,19,20]. Rojnuckarin et al [21] have cloned five serine proteases from the Thai T. albolabris venom gland cDNA library, and predicted there were two TLEs (i.e.…”
Section: Introductionmentioning
confidence: 99%